PENGETAHUAN, SIKAP, DAN PERILAKU TENTANG KONSUMSI SAYUR DAN BUAH PADA APARATUR SIPIL NEGARA (ASN) DI KABUPATEN BADUNG - D Dwiyantiningsih; Anak Agung Ngurah Kusumajaya; Anak Agung Gde Raka Kayanaya (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
ABSTRACTOne of community action for healthy life is related to dietary change to increase the consumption of vegetables and fruits. However, they are is still very low in the society. National Basic Health Research found that consumption of vegetables and fruits in the category of less in 2007 until 2013 showed that there was no significant change from 93.6% to 93.5%. This number similar in Province of Bali in 2007 and 2013 also found that the high percentage of less consumption of vegetables and fruit about 96,5% and 97,5% respectively. The study aims to determine knowledge, attitude, and behavior about consumption of vegetables and fruits in government officer of Badung Regency. This is a cross-sectional study using 60 samples. The study found that thare are 55,5% samples had enough knowledge about vegetables and fruits consumption. Most samples classified as having good attitude is as many as 55.0%. The behavior of consumption of vegetables is considered low that almost all samples consumed vegetables in amount 250 grams in a day about 98.3%. According to the type of fruits can be seen that most samples consume 2 types of fruits in a day as many as 45.0% with less category.Keywords: knowledge, attitude, and behavior, consumption vegetables and fruits